Revegetasi Lahan Bekas Tambang dengan Tanaman Multifungsi di Karang Panganten, Desa Gunungmasigit, Kabupaten Bandung Barat - Abdurahman, Oman; Sarasi, Vita; Afrullah, Yunardi (Warta LPM, 2023)
The uncontrolled sand, stone, limestone, and marble mining activities have caused damage to Karang Panganten in the Rajamandala karst area, West Bandung Regency, which is a geologically protected area in the form of a nature reserve. The resulting damage has had adverse effects on the community, such as the loss of clean water sources, environmental degradation, decreased air quality, and disruptions to the livelihoods of people dependent on natural resources in the area. Therefore, a Community Service Activity (PKM) was conducted by the Bandung Energy and Mining Polytechnic (PEP) from June to December 2022 with approximately 50 to 75 participants. The method used involved providing materials on organic fertilizer production using stacked buckets, greening the mining area by distributing and planting 140 multifunctional plant seedlings, namely moringa, bamboo, and balsa, renovating some slippery and steep footpaths, and installing plaques as a sign that the activity had been carried out. The results of this PKM activity include conveying an understanding of the importance of greening to achieve a balance between mining activities and environmental sustainability management, as well as increasing the community's knowledge of organic fertilizer production for optimal plant growth. This PKM activity indirectly contributes to the Citarum River Basin (DAS) conservation program, specifically the "Citarum Harum" program. Subsequent PKM activities can replicate this initiative in other villages in the Cipatat Subdistrict or other karst areas in West Bandung, as these areas are in great need of rehabilitation. The entire process can be modularized as a guide for future educational activities.